Možnosti 3D tlače v oftalmológii - prvé skúsenosti pri plánovaní stereotaktického rádiochirurgického zákroku u vnútroočného nádoru - Furdová, A; Furdová, Ad; Thurzo, A; Šramka, M; Chorvát, M; Králik, G (Ceska a slovenska oftalmologie, 2016)
UNLABELLED: Nowadays 3D printing allows us to create physical objects on the basis of digital data. Thanks to its rapid development the use enormously increased in medicine too. Its creations facilitate surgical planning processes, education and research in context of organ transplantation, individualization prostheses, breast forms, and others.Our article describes the wide range of applied 3D printing technology possibilities in ophthalmology. It is focusing on innovative implementation of eye tumors treatment planning in stereotactic radiosurgery irradiation.We analyze our first experience with 3D printing model of the eye in intraocular tumor planning stereotactic radiosurgery. KEY WORDS: 3D printing, model, Fused Deposition Modelling, stereotactic radiosurgery, prostheses, intraocular tumor.
Keywords: Radiosurgery; 3D tisk; nádory oka; plánování radioterapie pomocí počítače; Magnetic Resonance Imaging; lidé; Female; biologické modely; ženské pohlaví; Models, Biological; oftalmologie; Ophthalmology; magnetická rezonanční tomografie; Eye Neoplasms; Printing, Three-Dimensional; Humans; radiochirurgie; Radiotherapy Planning, Computer-Assisted